Pengembangan Media Pembelajaran Spinner Word Berbasis Kontekstual Untuk Siswa Kelas II di Sekolah Dasar - Desriarini Gui, Marsella (PT MEDIA JURNAL DAN PENDIDIKAN, 2023)
This development research aims to produce Spinner Word Learning Media products. The aims of this study were to: (1) explain the design of Spinner Word Learning Media for Indonesian Language Content for Class II Students; and (2) determine its validity. This development study uses the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Due to the many students are unable to engage in research, which is limited to individual trials. In this study, data was collected through a non-test method using a questionnaire. Quantitative and qualitative descriptive data analysis was used. The results of the development research include (1) a description of the development process of Word Spinner Learning Media; (2) Spinner Word Learning Media was declared valid based on the assessment of learning content experts at 90.9% with very good qualifications; 85.9% learning design experts with very good qualifications; and learning media experts at 90.6% with very good qualifications.